THE RELATIONSHIP BETWEEN KNOWLEDGE WITH BREAST SELF-EXAMINATION BEHAVIOR (SADARI) - Andayani, Hana Fitria; Nurliana, Irna; Arisara, Gita (PHSAJ - Public Health Sebelas April Journal, 2024)
The high prevalence of breast cancer in Indonesia is caused by late treatment at an early stage. Breast self-examination is an examination that is the cheapest and easiest to do to detect breast cancer early. This study aims to determine the relationship between knowledge and attitudes with breast self-examination behavior (SADARI) in grade 11 students at SMK Negeri 2 Sumedang in 2023. The design of this study is descriptive correlation with a crossectional approach. The population in this study was 552 and the sample size in this study was 85 people using the Stratified Random Sampling Technique. Data collection methods in this study using a questionnaire. Data analysis using univariate and bivariate analysis with chi-square statistical tests. The results showed 48 students (56.5%) had sufficient knowledge, and 68 students (80.0%) had unsupportive behavior. From the results of the chi-square test, it was found that there was a relationship between knowledge and SADARI behavior (p=0.005). It is expected that the school cooperates with health workers to provide counseling on SADARI to detect early breast cancer.